The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.abrep.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

“I cannot stand the boredom.” Binge drinking expectancies in adolescence

Abstract: Introduction: The main aim of this study is to improve our knowledge on binge drinking behavior in adolescents. In particular, we tested a model of predictors of binge drinking focusing on boredom proneness; we also examined the predictive and mediating role of drinking expectancies on binge drinking. Methods: A questionnaire designed to assess current drinking behavior, such as binge drinking, drinking expectancies and boredom proneness, was administered to 721 Italian adolescents (61% females) aged between 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
74
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 79 publications
7
74
0
5
Order By: Relevance
“…Addington and Addington (2007) and Cardoso et al (2008) had similarly found no difference in QOL between alcohol abusers and non-abusers among FEP and bipolar populations, respectively. Cardoso et al (2008) proposed that the self-report nature of the questionnaires may limit studies' abilities to (Addington & Duchak, 1997;Archie et al, 2013;Biolcati et al, 2016;Spencer, Castle, & Michie, 2002). These three themes were similarly found within our sample; individuals who had ever binged were more likely to agree that alcohol helps to enhance social activities and enables people to have more fun (enhancement); deal with stress (coping); and helps "break the ice" and create easier connections with friends (socializing).…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Addington and Addington (2007) and Cardoso et al (2008) had similarly found no difference in QOL between alcohol abusers and non-abusers among FEP and bipolar populations, respectively. Cardoso et al (2008) proposed that the self-report nature of the questionnaires may limit studies' abilities to (Addington & Duchak, 1997;Archie et al, 2013;Biolcati et al, 2016;Spencer, Castle, & Michie, 2002). These three themes were similarly found within our sample; individuals who had ever binged were more likely to agree that alcohol helps to enhance social activities and enables people to have more fun (enhancement); deal with stress (coping); and helps "break the ice" and create easier connections with friends (socializing).…”
Section: Discussionmentioning
confidence: 63%
“…Psychotherapy interventions utilizing motivational elements have shown efficacy in reducing alcohol use among persons with psychosis (Baker et al, ; Hulse & Tait, ); understanding the underlying motivations for drinking patterns will be beneficial for further tailoring therapeutic interventions. Previous research on reasons for alcohol use among populations with and without psychosis has consistently identified three key motivations: (a) enhancement/pleasure seeking; (b) coping with psychological distress or negative affect; and (c) socializing‐related motives (Addington & Duchak, ; Archie et al, ; Biolcati et al, ; Spencer, Castle, & Michie, ). These three themes were similarly found within our sample; individuals who had ever binged were more likely to agree that alcohol helps to enhance social activities and enables people to have more fun (enhancement); deal with stress (coping); and helps “break the ice” and create easier connections with friends (socializing).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations